Pelatihan Kewirausahaan Makanan Khas Budaya Karo di UD Silangit Kabanjahe Kabupaten Karo - Ingan Ukur Sitepu; Menanti Sembiring (CV. Ulil Albab Corp, 2023)
In this Millennial era, there are a lot of rapid changes resulting in every time our footsteps must also change quickly for a better direction. It cannot be denied that in the end changes are able to follow it and have a negative impact on those who are slow to respond. Of the many changes that have occurred, the most important changes to pay attention to are changes in human thinking patterns, changes in lifestyle, tastes and personal behavior, from children to adults, both in cities and villages which ultimately affect one's view of something. including changes in the mindset of our students today. The background of why entrepreneurship is necessary is to be able to look at a better future. With entrepreneurship, it is hoped that someone will be able to be independent, create jobs for others, and be the boss of their business. In other words, it is better to pay a salary than to be a salary person. It is necessary to create a climate that can change the mindset, both mental and motivation of parents, lecturers and students so that later their children are accustomed to creating jobs rather than looking for work. One way is to change the mentality and motivation that has been so embedded in every human being, especially in the Karo Culture Food Entrepreneurship Training UD Silangit Karo Regency.